The Impact of Monopoly Practices in Business Space in Indonesia According to Indonesian Regulations - Kusumawardana, Amanda Salsabila; Rani Apriani (Fakultas Hukum Universitas Djuanda, 2025)
Monopoly is a market situation in which there is only one business actor or one group of business actors who